2016
DOI: 10.1055/s-0042-111436
|View full text |Cite
|
Sign up to set email alerts
|

CCL2, CCL5, IL4 and IL15 Gene Polymorphisms in Women with Gestational Diabetes Mellitus

Abstract: Gestational diabetes mellitus (GDM) is a glucose intolerance that occurs during pregnancy. Several studies suggest that inflammation contributes to pregnancy-induced insulin resistance and the development of glucose intolerance. The aim of this study is to examine the association between the ,, and gene polymorphisms and the development of GDM. This study included 411 pregnant women who underwent a 75 g oral glucose tolerance test at 24-28 weeks of gestation. Participants were categorised into 2 groups accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…The diagnosis of GDM was made when one of the following plasma glucose values in the OGTT was met or exceeded: fasting plasma glucose 92 mg/dL (5.1 mmol/L), 1-h plasma glucose 180 mg/dL (10.0 mmol/L) and 2-h plasma glucose 153 mg/dL (8.5 mmol/L) [10]. Among the pregnant women with GDM, 152 (75%) were treated with diet control alone throughout the pregnancy, whereas the remaining 52 (25%) were treated with diet control and insulin until delivery [11]. The study was approved by the ethics committee in Pomeranian Medical University, Szczecin, Poland, and written informed consent was obtained from all subjects.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis of GDM was made when one of the following plasma glucose values in the OGTT was met or exceeded: fasting plasma glucose 92 mg/dL (5.1 mmol/L), 1-h plasma glucose 180 mg/dL (10.0 mmol/L) and 2-h plasma glucose 153 mg/dL (8.5 mmol/L) [10]. Among the pregnant women with GDM, 152 (75%) were treated with diet control alone throughout the pregnancy, whereas the remaining 52 (25%) were treated with diet control and insulin until delivery [11]. The study was approved by the ethics committee in Pomeranian Medical University, Szczecin, Poland, and written informed consent was obtained from all subjects.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, the association between polymorphisms and gestational diabetes was studied in three models: additive (number of variant alleles = 0, 1, or 2 for each subject), dominant (variant homozygotes and heterozygotes vs. wildtype homozygotes) and recessive (variant homozygotes vs. heterozygotes and wildtype homozygotes) [10][11][12][13][14][15][16][17]. The best fit was observed for the additive model.…”
Section: Discussionmentioning
confidence: 99%
“…Genotypes were assigned using all data from the study simultaneously. Details of genotyping methods are described in previous papers [10][11][12][13][14][15][16][17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SNPs within the coding and signal sequences can affect gene transcriptional activity, and then change the production of proteins [14]. Several studies have reported that altered cytokines expression are related to the severity and progression of the GDM [15,16].…”
Section: Introductionmentioning
confidence: 99%